2019
DOI: 10.3390/antibiotics8040265
|View full text |Cite
|
Sign up to set email alerts
|

Short Chain Fatty Acids Commonly Produced by Gut Microbiota Influence Salmonella enterica Motility, Biofilm Formation, and Gene Expression

Abstract: Short chain fatty acids (SCFAs) are commonly produced by healthy gut microbiota and they have a protective role against enteric pathogens. SCFAs also have direct antimicrobial activity against bacterial pathogens by diffusion across the bacterial membrane and reduction of intracellular pH. Due to this antimicrobial activity, SCFAs have promising applications in human health and food safety. In this study, the minimum inhibitory concentrations (MICs) of four SCFAs (acetic acid, butyric acid, propionic acid, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 45 publications
2
67
0
Order By: Relevance
“…The effect of SCFA against intestinal pathogens, such as Salmonella species, E. coli and Campilobacter jejuni, has been investigated. SCFA modulate growth, motility, biofilm formation and quorum sensing by these organisms (Nakamura et al, 2009;Amrutha et al, 2017;Jacobson et al, 2018;Lamas et al, 2019). Remarkably, it has also been shown that subinhibitory concentrations of these SCFA can alter gene expression of pathogenic bacteria in such a way that virulence is favored (Lamas et al, 2019).…”
Section: Fatty Acid Metabolites Serve An Antimicrobial Functionmentioning
confidence: 99%
“…The effect of SCFA against intestinal pathogens, such as Salmonella species, E. coli and Campilobacter jejuni, has been investigated. SCFA modulate growth, motility, biofilm formation and quorum sensing by these organisms (Nakamura et al, 2009;Amrutha et al, 2017;Jacobson et al, 2018;Lamas et al, 2019). Remarkably, it has also been shown that subinhibitory concentrations of these SCFA can alter gene expression of pathogenic bacteria in such a way that virulence is favored (Lamas et al, 2019).…”
Section: Fatty Acid Metabolites Serve An Antimicrobial Functionmentioning
confidence: 99%
“…A previous study discussed an additional beneficial effect of offering a coarse compound feed to broilers reflected in the increased synthesis of butyrate in the large intestine [ 56 ]. This butyrate can reduce the invasive activity of Salmonella [ 32 , 57 ]. There is also evidence that the use of intact cereal grains in compound feed has a positive effect on the microflora in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs have direct antimicrobial activity by diffusing through bacterial membranes and lowering intracellular pH. SCFAs have promising applications in human health and food safety due to their antimicrobial activity [ 79 ]. Clostridia SCFAs are important metabolites that inhibit S. Typhimurium growth in mice intestines [ 73 ], pathogenic E. coli strain growth in streptomycin-treated mice [ 80 ], and C. difficile growth in humans [ 81 , 82 ].…”
Section: The Intestinal Microbiota Showed Colonization Resistance To Pathogensmentioning
confidence: 99%